Sensitivity of xylem vessel size and frequency to rainfall and temperature: implications for palaeontology - February, Ed (Bernard Price Institute for Palaeontological Research, 1993)
Based on the xylem vessel size and frequency in fossil wood, a number of studies have developed theories on climate change through time. The basic premise of these studies is that xylem vessel size decreases while vessel frequency increases with intensifying aridity. In this paper the relationship between rainfall and xylem vessel size and frequency is examined in two extant tree species. The results indicate that rainfall is related positively to vessel diameter and negatively to vessel frequency in Combretum apiculatum and Protea caffra. Xylem vessel size of both species is between 50 and 100 µm. However, the two species exhibit different responses to rainfall in that P. caffra has much smaller diameter vessels than C. apiculatum in high rainfall areas. These differences indicate that the potential for using xylem anatomy as a palaeoclimatic indicator has not been fully utilised. A more precise picture of climate change through time is possible with a more refined statistical analysis of reliably identified fossil wood.
Keywords: wood anatomy; fossil wood